Human Security: A Human Rights Approach to National Security? - Serrano, Evelyn B.; de Mesa, Max M. (Kasarinlan: Philippine Journal of Third World Studies; Vol 19 No 1 (2004): Human Security in Conflict Situations, 2007)
This paper discusses the evolution of a more inclusive perspective of human rights encompassing not only civil and political rights but also economic, social and cultural rights. Serving as the anchor of a rights-based perspective of national security, the convergence of human security and human rights becomes more imperative with changes taking place in the local and international contexts. The study provides an overview of the development of the human rights discourse from the conclusion of the Second World War with the signing of the Universal Declaration of Human Rights (UDHR) in 1948 to the forging of the International Covenant on Civil and Political Rights (ICCPR) and the International Covenant on Economic, Social and Cultural Rights (ICESCR). The study also presents the diverging appreciation and enforcement of both covenants citing the case of Nepal where the perpetration of human rights violations of both state and non-state actors using arms and coercive force have exacerbated the physical as well as the social and economic insecurity of its people.
Keywords: human rights; human security; national security